EFEKTIVITAS PENERAPAN MEDIA PUZZLE PECAHANTERHADAP HASIL BELAJAR MATEMATIKASISWA KELAS IV SDN 04 KOTO BARU - Suci Rahma Putri; Rendi Marlianda; Rina Faiza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Problems in Mathematics learning in the discussion of fractions, where there is a lack of student learning outcomes in mathematics on fractions. Students still have little knowledge about fractions, students have difficulty understanding fractions. Through this problem, the aim of this research is to overcome the low student learning outcomes. To overcome this, interesting and appropriate media is needed so that students can easily understand the material. Therefore, researchers will apply fraction puzzle media. The type of research used in this research is the experimental method. Experimental research is research conducted to reveal the relationship between two other variables. There are several types of Pre-Experimental Design, namely One-Shot Case Study, One-Group Pretest-Posttest Design, and Intact-Group Pretest-Posttest Design (initial test-single group final test). In this study, an initial test (Pretest) was given before treatment was given, after treatment, acting out was given a final test (Posttest). Because by knowing this you can compare the results more accurately. This research was carried out at SDN 04 Koto Baru in class IV in the even semester of the 2023/2024 academic year. The population in this study was 20 elementary school students. The data collection instruments used used independent and dependent variables. Development of instruments used for validity testing, reliability testing, level of difficulty testing. The data collection technique used was an initial test (pre-test) and a final test (post-test). The data analysis technique for this research uses the Normality Test and hypothesis testing. Based on the results obtained, the significance of the paired samples t test showed that it was significant at 0.000 at a significance level of 0.005. The calculation results obtained sig <a (0.000 <0.005) which means the t test is not in the Ho acceptance area so it can be concluded that Ho is rejected and Ha is accepted. Thus the hypothesis proposed in this research is proven. So "there is a significant influence of the use of fraction puzzle media in the Mathematics subject Fraction material on the learning outcomes of class IV students at SDN 04 Koto Baru".